State-feedback design for nonlinear saturating systems - Valmorbida, G; Papachristodoulou, A (Institute of Electrical and Electronics Engineers, 2021)
This paper presents strategies for state-feedback control law design of non-linear control laws with saturating inputs. The input constraints are handled by considering a generalized local sector inequality allowing to study non-symmetric saturation bounds. A numerical formulation is presented for polynomial systems and is based on the solution of Lyapunov inequalities with sum-of-squares programming. Numerical results illustrate the proposed method.